CORRUPTION RISKS AND RISKS IN HIGHER EDUCATION INSTITUTIONS, THEIR DESCRIPTION (International Educators Conference, 2025)
Corruption undermines the atmosphere of trust in educational institutions. If students notice that their teachers or the administration of a higher education institution are involved in corruption, their confidence in education is undermined. This reduces the effectiveness of the educational process, as constructive communication and mutual respect between students and educators are lost. In the absence of trust between educators and students, the educational system remains only nominal.